2019
DOI: 10.3390/ijms20164052
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Properties of Linagliptin: Focus on Biochemical Mechanisms in Cerebral Ischemia, Vascular Dysfunction and Certain Neurodegenerative Diseases

Abstract: Linagliptin is a representative of dipeptidyl peptidase 4 (DPP-4) inhibitors which are registered and used effectively in a treatment of diabetes mellitus type 2. They increase the levels of active forms of endogenous incretins such as GLP-1 and GIP by inhibiting their enzymatic decomposition. Scientific reports suggest beneficial effects of linagliptin administration via immunological and biochemical pathways involved in neuroprotective processes of CNS. Linagliptin’s administration leads to a decrease in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 127 publications
0
14
0
Order By: Relevance
“…Linagliptin (marketed under trade names Tradjenta) is an inhibitor of dipeptidyl peptidase-4 (DPP-4) that has beneficial effects on impaired insulin signaling caused by Aβ in the SK-N-MC neuronal cells ( Kornelius et al, 2015 ). Linagliptin activates the AMPK/SIRT1 pathway that further attenuates the mitochondrial dysfunction, and excessive ROS production caused due to aggregation of Aβ ( Kornelius et al, 2015 ; Wiciński et al, 2019 ). This proves that DPP-4 inhibitors possess therapeutic potential for AD pathogenesis.…”
Section: Sirt1 and Sirt2 In Alzheimer’s Diseasementioning
confidence: 99%
“…Linagliptin (marketed under trade names Tradjenta) is an inhibitor of dipeptidyl peptidase-4 (DPP-4) that has beneficial effects on impaired insulin signaling caused by Aβ in the SK-N-MC neuronal cells ( Kornelius et al, 2015 ). Linagliptin activates the AMPK/SIRT1 pathway that further attenuates the mitochondrial dysfunction, and excessive ROS production caused due to aggregation of Aβ ( Kornelius et al, 2015 ; Wiciński et al, 2019 ). This proves that DPP-4 inhibitors possess therapeutic potential for AD pathogenesis.…”
Section: Sirt1 and Sirt2 In Alzheimer’s Diseasementioning
confidence: 99%
“…In contrast, DPP4 (also known as T cell activation antigen CD26) can more confidently be localized to human CNS in an age-dependent manner and is a protein implicated in immunologic signaling, processing/inactivation of neuropeptides, and glucose homeostasis. It is the target for inhibition by gliptin therapies in diabetes, which are also in trial for dementia and stroke (Wicinski et al 2019 ). The DPP4 protein has been detected in abundance in human fetal and perinatal brains and in neuroblasts and neurons, capillaries, ependyma, and choroid plexus (Bernstein et al 1987 ).…”
Section: Basic Biology Of Coronavirusesmentioning
confidence: 99%
“…We also confirmed that the increased vesicles may result from both caveolin‐ and clathrin‐mediated endocytosis pathways. Diabetes elevates the expression of HIF‐1α and vascular endothelial growth factor (VEGF) in the ischemic cerebral microvasculature, 38,50,51 which is accompanied by the disruption of the BBB, increased infarct volume, severe edema formation, and exacerbated neurological deficits. Specific inhibition of endothelial HIF‐1α could partially reverse the damaging effects of diabetes on cerebrovascular injury, suggesting that HIF‐1α activation is one important mechanism underlying increased BBB permeability 38 .…”
Section: Discussionmentioning
confidence: 99%